O impacto da institucionalização de sistemas informatizados de gestão sobre a redução da vulnerabilidade à corrupção em órgãos públicos de saúde no Brasil - Magnagnagno, Odirlei Antonio (2020)
Information and Communication Technologies (ICTs) have great potential in combating corruption. In this thesis, it has been proposed a model that considers the relationships between computerized management systems, vulnerabilities to corruption and the intention to commit acts of corruption. Management practices have benefited from the use of technologies, as these have been used to improve the management of organizations, mainly in the inclusion of information in the decision-making process. In addition, computerized management systems can contribute to reducing vulnerabilities to corruption by recording information, updating data, control and limits for operations. Vulnerability is the use or exploitation of weakness or failure, resulting in unwanted events, whether intentional or accidental. That is, vulnerability to corruption can lead an individual or a group to commit acts of corruption. Management measures often fall short in relation to corruption, because individual characteristics, associated with honesty and creation or alteration of laws stand out. In this sense, the main objective of the thesis is to propose a model for the relationship between computerized management systems, corruption vulnerabilities and the intention to commit acts of corruption, seeking to identify the influence of the institutionalization of computerized management systems in the intention to commit acts of corruption in public organizations. For the construction of the theoretical model, institutional theory and the theory of planned behavior were used. The institutional theory with regard to computerized management systems, seeks relationships vulnerable to corruption such as internal control, bureaucracy, accountability and transparency, through four hypotheses. The theoretical model also sought the relationship of vulnerabilities to corruption with intention of committing acts of corruption, based on the theory of planned behavior, using four hypotheses, totaling eight hypotheses. Qualitative and quantitative methods of data analysis were used, within an descriptive phase, through a systematic review of literature to search and identify vulnerabilities to corruption and an exploratory phase, which tested the relationships of variables, using the technique of Partial Least Squares (Partinal Least Squares - PLS). A face and content validation was carried out with eight specialists from different areas. A pilot study was also carried out with 87 valid responses, and after the adjustments, new data were collected, both throughout a survey. Data collection took place with public officials from the health departments of the seven largest municipalities in the State of Paraná and totaled 355 valid responses. As a result, the study confirmed seven of the model's eight hypotheses. The only relationship that has not been validated concerns transparency and the intention to commit acts of corruption. However, the general hypothesis that states that institutionalized computerized management systems reduce the intention to commit acts of corruption has been confirmed. In addition to confirming the relationship between the institutionalization of computerized management systems, vulnerabilities to corruption and the intention to commit acts of corruption, the thesis presents a theoretical model that can be tested in other spheres and public organizations, to confirm and strengthen the relationship between variables. A practical contribution is to show the importance of investing and institutionalizing computerized management systems, due to the strong relationship with the decrease in the intention to commit acts of corruption, through increased control. The study was limited to the municipal health departments of the state of Paraná.